A comparative measurement technique of nanoparticle heating for magnetic hyperthermia applications. (14th November 2017) - Drayton, A; Zehner, J; Timmis, J; Patel, V; Vallejo-Fernandez, G; O'Grady, K
Abstract: We describe a method for the determination of the heating power of magnetic nanoparticle colloids which have potential for application in the remedial treatment of malignant and non-malignant tumours. The method is based upon a comparison between the heating power observed when the colloid is exposed to a radio frequency magnetic field and that which is observed using a resistive electrical heater. A new design of the measurement cell has been made which has the advantages of reducing or eliminating the effects of convection, ensuring the measurement is made in a magnetic field of known uniformity and that the heat losses in the system are constant and minimized under both magnetic and Joule heating.